Exploring Discord as an Educational Tool: Student Insights and Perspectives - Ai, Lia; Yuanfang, Xue (International Journal of Educational Technology and Artificial Intelligence, 2025)
The rise of social media has significantly influenced various aspects of daily life, including education. Among these platforms, Discord stands out due to its interactive features and community-building capabilities. Initially designed for communication in gaming contexts, Discord has recently attracted interest as a potential educational tool. This study explores its educational viability by examining student experiences and perceptions.Utilizing a mixed-methods approach, the research surveyed 50 students from the National University – Dasmariñas, combining quantitative data on Discord usage patterns with qualitative insights into its educational effectiveness. The survey revealed that 70% of respondents used Discord frequently, with 60% employing it for learning. Preferred subject areas included Science and Math, aligning with Mayer’s Cognitive Theory of Multimedia Learning, which highlights the advantages of combining auditory and visual information. Qualitative data offered deeper insights into student motivations, highlighting Discord’s accessibility, informal nature, and engaging format as key factors. Students appreciated the platform’s ability to present complex topics in bite-sized, digestible formats. However, concerns were raised about the limitations of short-form content, particularly regarding depth and accuracy. The study concludes that while Discord holds significant potential as a supplementary educational tool, particularly for initial knowledge acquisition and visual learning, it should be thoughtfully integrated with traditional learning methods to address its limitations.